2016
DOI: 10.1016/j.psychres.2016.06.044
|View full text |Cite
|
Sign up to set email alerts
|

Effect of alcohol and illicit substance use on verbal memory among individuals with bipolar disorder

Abstract: Background Cognitive impairment is a well-established feature of bipolar disorder (BD). Comorbid BD and substance use leads to poor psychosocial and clinical outcomes. However, knowledge on the neurocognitive functioning of individuals with dual diagnosis is limited. The aim of this study is to assess the cognitive performance of subjects with BD, BD with comorbid alcohol use disorder (AUD), and BD with comorbid illicit substance use disorders (SUD) as compared to healthy individuals. Methods We included 270… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 64 publications
3
12
0
1
Order By: Relevance
“…Similar to our previous study, we found poorer 1‐year outcomes in executive functioning in patients with a history of substance/alcohol abuse ; however, between one and 3 years, these patients made preferential cognitive gains so that they were indistinguishable from those without history of alcohol/substance abuse at the 3‐year point. These findings are generally consistent with a body of literature showing that alcohol and substance abuse comorbidity in bipolar disorder associates with more prominent cognitive impairment . However, the present data suggest that history of substance use may delay, rather than arrest the early recovery in cognitive functioning.…”
Section: Discussionsupporting
confidence: 92%
“…Similar to our previous study, we found poorer 1‐year outcomes in executive functioning in patients with a history of substance/alcohol abuse ; however, between one and 3 years, these patients made preferential cognitive gains so that they were indistinguishable from those without history of alcohol/substance abuse at the 3‐year point. These findings are generally consistent with a body of literature showing that alcohol and substance abuse comorbidity in bipolar disorder associates with more prominent cognitive impairment . However, the present data suggest that history of substance use may delay, rather than arrest the early recovery in cognitive functioning.…”
Section: Discussionsupporting
confidence: 92%
“…This greater comorbidity might be attributed to our long-term-followed and complex study population. Comorbid alcohol and substance use disorders were speculated to be frequent in bipolar disorder (Cardoso et al, 2016). Current study showed lower ratios of these disorders in study group, which might be related to cultural and social determinants, and higher numbers of female patients.…”
Section: Discussionmentioning
confidence: 49%
“…Genetic and family studies have likewise suggested a considerable overlap and interaction between the two disorders, which raises the likelihood probability that early onset bipolar disorder and substance abuse disorder share at least some common genetic vulnerabilities [ 136 ]. People with BD are more exposed to substance use disorders (SUDs: non-medical use of, or dependence on drugs and/or alcohol), while, viewed from the opposite perspective, a history of SUDs is associated with an earlier onset of BD [ 131 , 137 ]. People diagnosed with BD are more susceptible to a greater use of cocaine, amphetamines, opiates, cannabinoids and hallucinogens, in comparison with other psychiatric disorders such as schizophrenia [ 138 , 139 , 140 , 141 , 142 , 143 ].…”
Section: Neuropsychiatry and Endometriosis: The State Of The Artmentioning
confidence: 99%